COLLABORATION BETWEEN FAMILIES AND SCHOOLS TO INSTILL RESPECT FOR ADULTS IN PRIMARY SCHOOL STUDENTS - Esemuratova, Т.А.; Matmuratova, G.K.; Utepova, G.S. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The article looks at the educational and psychological possibilities of teaching elementary school students to respect adults and how they can try to organize some activities on their own by acting like older family members.
Keywords: family; respect. skills; qualities of adult respect; spirituality; and morality